Democratic Regression in Brazil under the Bolsonaro Presidency - Ziegenhain, Patrick; Kemalasari, Nyi (Jurnal Demokrasi dan Politik Lokal, 2024)
In this paper we analysed the quality of democracy during the presidency of Brazilian President Jair Bolsonaro between 2018 and 2022. Our research question was whether an erosion of democracy, or more precisely a reduction of the quality of Brazilian’s democracy, took place during that time or not. To answer these questions, we used relevant democracy criteria as analytical tools. Methodologically, this study we conducted a thorough literature review and an expert interview with a Brazilian social scientist. As a result, we concluded that based on the findings in the fields of vertical accountability, political rights, civil liberties, and horizontal accountability there was indeed a decline of democratic quality during Bolsonaro’s presidency.